2019
DOI: 10.5539/jas.v11n2p169
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cymbopogon flexuosus Biomass and Essential Oil Production With Organic Manures

Abstract: Cymbopogon flexuosus is a medicinal species with relevant commercial value and widely used in flavors, fragrances, toiletries, cosmetics, soaps, detergents, and pharmaceutical products. The objective of this study was evaluate the effects of different doses and sources of two manures and one compost on plant growth, leaf nutrient accumulation, content, yield, and chemical composition of the essential oil. The sources were cattle manure, quail manure, and organic compost applied in four doses and control treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(34 reference statements)
0
0
0
Order By: Relevance
“…La vandula dentata has had higher content and yield when grown with organic fertilizer (LUZ et al, 2016). Th e C. flexuosus essential oil yield has been higher when using quail manure than when using cattle manure (LOPES et al, 2019). Bibiano et al (2019) found that the highest essential oil yields of D. ambrosioides were obtained with 12 kg m -2 cattle, 6 to 12 kg m -2 chicken or 9 kg m -2 quail manure.…”
Section: Manuresmentioning
confidence: 99%
See 2 more Smart Citations
“…La vandula dentata has had higher content and yield when grown with organic fertilizer (LUZ et al, 2016). Th e C. flexuosus essential oil yield has been higher when using quail manure than when using cattle manure (LOPES et al, 2019). Bibiano et al (2019) found that the highest essential oil yields of D. ambrosioides were obtained with 12 kg m -2 cattle, 6 to 12 kg m -2 chicken or 9 kg m -2 quail manure.…”
Section: Manuresmentioning
confidence: 99%
“…Leaf Mg (0.3 to 0.4%) and S (0.2 to 0.3%) were similar between all treatments. According to Lopes et al (2019), Cymbopogon flexuosus plants fertilized with quail manure accumulated higher concentrations of macroand micronutrients in the leaf than those fertilized with cattle manure or organic compost.…”
Section: Manuresmentioning
confidence: 99%
See 1 more Smart Citation